O equilíbrio econômico-financeiro dos contratos de concessão de rodovias federais e estaduais sob a égide da Lei 8.987/95 - Matos, Fernanda de Mello [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The purpose of this dissertation is to analyze the economic and financial balance of the concession of federal and state highways in the light of Law 8.987/95. The law 8.987/95, known as General Law of Concessions, provides for the concession and permission of the provision of public services provided for in art. 175 of the Federal Constitution. From the 80s, there was the Brazilian trajectory of privatization of public services, where the state has delegated the provision of public services to the private sector, including services related to infrastructure, such as highways. The State thus increasingly takes on a role of manager of public services, through regulation, which is the preferred option of indirect intervention by the State, not directly assuming the exercise of business activities. Arises, therefore, the institute of public service concessions which aims to regulate the relationship between the state and the concessionaire in providing public services. The concession of public services is characterized when competing cumulatively transfer the exercise of a public service to the private person who accepts rendering it, in his own name and at your own risk, paying them by the actual operation of the service, basically fee charged by the service users. Due to the long duration of these contracts, usually between twenty and thirty, is vital for the continuity of public service, the prediction of mechanisms to ensure the grantor and dealer for the permanence of conditions originally agreed. The economic-financial equation of the contract reflected in the balance between the obligations assumed by the concessionaire, the charges that will be incurred and consideration for the granting authority, or the remuneration of the concessionaire. However, there are a number of factors that can disrupt the concession of highways, such as the inclusion of new investments, the incidence of new taxes, the occurrence of subsequent events,...

A presente dissertação se propõe à análise do equilíbrio econômico-financeiro dos contratos de concessão de rodovias federais e estaduais à luz da Lei 8.987/95. A Lei 8.987/95, conhecida como Lei Geral das Concessões, dispõe sobre o regime de concessão e permissão da prestação de serviços públicos previsto no art. 175 da Constituição Federal. A partir da década de 80, houve a trajetória brasileira de desestatização de alguns serviços públicos, onde o Estado delegou a prestação de alguns serviços públicos à iniciativa privada, entre eles, serviços relacionados à infraestrutura, como no caso das rodovias. O Estado, assim, cada vez mais, vai assumindo um papel de gestor dos serviços públicos, através da regulação, que consiste na opção preferencial do Estado pela intervenção indireta, não assumindo diretamente o exercício das atividades empresariais. Surge, portanto, o instituto da concessão de serviços públicos que visa disciplinar a relação entre Poder Concedente e concessionária na prestação de serviços públicos. O contrato de concessão de serviços públicos caracteriza-se quando ocorre a transferência do exercício de um serviço público à pessoa privada que aceita prestá-lo, em nome próprio e por sua conta e risco, remunerando-se pela própria exploração do serviço, basicamente mediante tarifa cobrada dos usuários do serviço. Em razão da longa duração desses contratos, geralmente, entre vinte e trinta anos, é vital para a própria continuidade do serviço público, a previsão de mecanismos que garantam para o concedente e concessionário a permanência das condições inicialmente pactuadas. A equação econômico-financeira do contrato traduz-se no equilíbrio entre as obrigações assumidas pelo concessionário, os encargos que serão suportados e a contraprestação devida pelo concedente, ou seja, a remuneração do concessionário. Entretanto, existe...
Keywords: Direito administrativo; Concessões administrativas - Brasil; Rodovias - Aspectos econômicos; Pedágio; Administração pública; Contratos administrativos; Law